Association of ABO gene mutations resulting in a rare B subgroup - Sousa, N.; Anicchino-Bizzacchi, J. M.; Leite, E. M.; Locatelli, M. F.; Albuquerque, D.; Costa, F. F.; Castro, M. L. (Blackwell Publishing, 2005)
Background and Objectives B subgroups are rare and the genetic analysis reported to date has been limited.Materials and Methods Serological and molecular investigations were performed in blood from a B-subgroup donor.Results Red cells did not react with anti-B and anti-AB reagents. However, cells absorbed anti-B. Red cells presented positive reactions with anti-H, and saliva secreted H substance. The molecular study demonstrated a B allele with the substitutions 467C>T, 646T>A, 681G>A, 771C>T, 796C>A, 803G>C, 829G>A and an 0 allele with the sequence of 002.Conclusions It is probable that the presence in exon 7 of some of the 002 substitutions could have weakened the enzymatic activity of the encoded B transferase.
Keywords: ABO; B subgroup; blood group; genotyping; molecular biology